2010
DOI: 10.1016/j.ydbio.2010.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic imaging of mammalian neural tube closure

Abstract: Neurulation, the process of neural tube formation, is a complex morphogenetic event. In the mammalian embryo, an understanding of the dynamic nature of neurulation has been hampered due to its in utero development. Here we use laser point scanning confocal microscopy of a membrane expressed fluorescent protein to visualize the dynamic cell behaviors comprising neural tube closure in the cultured mouse embryo. In particular, we have focused on the final step wherein the neural folds approach one another and sea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
128
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 133 publications
(135 citation statements)
references
References 29 publications
6
128
0
1
Order By: Relevance
“…To enclose the lumen, ECs at the edges of the migrating sheet bend inwards, folding around the luminal space and therefore the blood stream. This morphogenetic process is very similar to the closure of the neural tube (Colas and Schoenwolf, 2001;Pyrgaki et al, 2010), suggesting a conserved role of this mechanism in lumen formation.…”
Section: Discussionmentioning
confidence: 72%
“…To enclose the lumen, ECs at the edges of the migrating sheet bend inwards, folding around the luminal space and therefore the blood stream. This morphogenetic process is very similar to the closure of the neural tube (Colas and Schoenwolf, 2001;Pyrgaki et al, 2010), suggesting a conserved role of this mechanism in lumen formation.…”
Section: Discussionmentioning
confidence: 72%
“…This could alter tissue tension or gradients of soluble factors, or suggest a distinct molecular mechanism active in mice. Live-imaging studies of neural tube closure have revealed both zipper-like and button-like mechanisms (Pyrgaki et al, 2010) and might provide insights into mechanisms underlying dorsal aorta fusion. It will be important to use the improved imaging methods established here to further delineate the mechanisms underlying these novel observations.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work by several laboratories, including our own, has shown that mouse embryos can be cultured and imaged using light microscopy at early post-implantation stages prior to the formation of the chorioallantoic placenta, thereby revealing novel dynamic events required for early development (Garcia et al, 2011a;Jones et al, 2002;Kwon et al, 2008;Pyrgaki et al, 2010;Stuckey et al, 2011;Trichas et al, 2012;Udan et al, 2013). As these embryos are very delicate and expand significantly during development, which poses serious complications for lightsheet imaging, we developed a new method for mounting mouse embryos from E6.5-8.5 for multi-angle, light-sheet microscopy to enable long-term imaging of growing embryos at a range of postimplantation stages.…”
Section: Introductionmentioning
confidence: 98%
“…Recent advances in mouse embryo ex utero culture techniques have allowed for live imaging of NT closure and hence a more dynamic evaluation of cellular behaviors during this process. In such a study of cranial NT closure, cellular projections were also seen in the gap between the neural folds (Pyrgaki et al, 2010).…”
Section: Histological Studies Of Neural Tube Fusionmentioning
confidence: 99%